2014
DOI: 10.4028/www.scientific.net/kem.622-623.879
|View full text |Cite
|
Sign up to set email alerts
|

A New Rolling Model for Three-Roll Rolling Mills

Abstract: During the last 90 years, a lot of works have been published about rolling theories for the two-roll rolling process (2RP). In the last decades, the three-roll process (3RP) has become a significant technique in the production of wire rod and bars, as it allows to cover a wide range of finished dimensions with one pass design, or to realize very close tolerances, depending on the pass design method used (free size rolling or high precision rolling). Horihata and Motomura [2] made use of the upper bound theorem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…flat pass; h0L -h1L: eq. entry and exit height of section [9] The well-known solution acc. to Alexander [15] in Fig.…”
Section: Calculation For 2-roll Passesmentioning
confidence: 99%
“…flat pass; h0L -h1L: eq. entry and exit height of section [9] The well-known solution acc. to Alexander [15] in Fig.…”
Section: Calculation For 2-roll Passesmentioning
confidence: 99%
“…Nardini et al [3] described the general process and showed a reduced spreading characteristic of the 4RP by means of Finite Element calculations. Avellino et al [4] showed a control system for the 4RP rolling block, where the working roll diameter was calculated according to the rolling theory of the 3RP [5].…”
Section: Intr Introduction Oductionmentioning
confidence: 99%
“…It is a rolling process in which material is shaped by three rolls in three directions, everyone of which is inclined to the others at 120 0 [1,2]. Three-roll rolling process has various advantages such as easy flow control, small space requirement, and comparatively uniform deformation, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The restriction of the material imposed by the shape of caliber rolls in the three-roll rolling process is greater than that in the two-roll rolling process. The accuracy of the shape of products made by the three-roll rolling process is considered to be higher than that of the two-roll rolling process [1][2][3].…”
Section: Introductionmentioning
confidence: 99%